ANALYSIS OF THE IMPACT OF THE PLANNED SEWAGE DISCHARGE FROM THE 'NORTH' POWER PLANT ON THE VISTULA WATER QUALITY - Wielgat, Paweł; Zima, Piotr (International Multidisciplinary Scientific GeoConference SGEM, 2016)
The paper presents results of analysis of the industrial sewage discharge impact from the 'North' Power Plant on the Vistula water quality around 45+330 of the river kilometer. For the analysis, the two-dimensional models of flow, impurities and temperature transport were used. Hydrological conditions of the analyzed section of the river, characteristic flows and bathymetry of the riverbed in the first instance were defined. the calculation of the velocity distribution at steady flow conditions were carried out for the characteristic flows as the least favorable due to the discharge of pollutants. For this purpose, a simplified, two-dimensional kinematic model for the variable depth of flow was used. The analysis of the impact of the discharge of impurities under steady flow of water was performed by solving an equation of unsteady transport of pollution. Numerical simulations were carried out for: temperature, BOD, DO, total suspension, TOC, biogenic compounds, sulfates, chlorides and metals. The analysis was subject to the distribution of the concentration of contaminants in the discharge site, as well as its range along the river bank. In order to determine the concentration of individual pollution indicators in the discharge location, measurements of their concentration in different seasons were carried out. These results were the initial condition in conducting numerical simulations. The analysis made it possible to demonstrate that the concentration discharged into the Vistula river pollution does not exceed the limit values for each of the indicators.